Risken för spridning av röta vid förröjning i granskog i södra Sverige - Carlsson, Torbjörn (SLU/Southern Swedish Forest Research Centre, 2007)
Root rot causes large economical losses for Swedish forestry. The spread of root rot can partly be prevented by treating the spruce stumps in thinnings. Late pre-commercial thinning (PCT) is one of the forestry measures where stump treatment is not used. Late PCT can be defined as: The act of cleaning the stand with the aim of improving accessibility and sight within the stand, and so to increase the mean stem´s volume during the first conventional thinning.